2020
DOI: 10.1186/s13567-020-00746-4
|View full text |Cite
|
Sign up to set email alerts
|

Marek’s disease vaccines-induced differential expression of known and novel microRNAs in primary lymphoid organ bursae of White Leghorn

Abstract: Marek's disease (MD) is a contagious disease of domestic chickens caused by MD viruses. MD has been controlled primarily by vaccinations, yet sporadic outbreaks of MD take place worldwide. Commonly used MD vaccines include HVT, SB-1 and CVI988/Rispens and their efficacies are reportedly dependent of multiple factors including host genetics. Our previous studies showed protective efficacy of a MD vaccine can differ drastically from one chicken line to the next. Advanced understanding on the underlying genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The highly inbred line 6 3 and line 7 2 chickens used in this study, sharing a common major histocompatibility complex haplotype (B*2), strikingly differ in their ability to convey protective efficacy by up to 40% in response to CVI988/Rispens and up to 82% in response to HVT vaccination against very virulent plus MDV challenge [17,72]. The observed phenotypic differences in the ability to convey protective efficacy in response to vaccination against MDV-induced tumor formation may result from a rather complex mechanistic system potentially involving host genomic and epigenomic variation and vaccine by chicken line interactions [61,73]. This point is well indicated, in turn, by the fact that the MD vaccine's immunologic mechanism of protection remains poorly understood [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly inbred line 6 3 and line 7 2 chickens used in this study, sharing a common major histocompatibility complex haplotype (B*2), strikingly differ in their ability to convey protective efficacy by up to 40% in response to CVI988/Rispens and up to 82% in response to HVT vaccination against very virulent plus MDV challenge [17,72]. The observed phenotypic differences in the ability to convey protective efficacy in response to vaccination against MDV-induced tumor formation may result from a rather complex mechanistic system potentially involving host genomic and epigenomic variation and vaccine by chicken line interactions [61,73]. This point is well indicated, in turn, by the fact that the MD vaccine's immunologic mechanism of protection remains poorly understood [74].…”
Section: Discussionmentioning
confidence: 99%
“…The 6 3 and 7 2 lines share a common major histocompatibility complex haplotype (B*2) but differ in susceptibility to avian leukosis virus infection and in resistance to MD [19,59]. Our recent studies revealed that MDV infection induced differential expression of nineteen and nine miRNAs in the two genetic lines of birds, respectively [60], and the MD vaccine HVT and CVI988/Rispens induced differential expression of four and thirteen exclusive microRNAs in the 6 3 line birds, and 0 and one miRNA in the 7 2 line birds, respectively [61]. To advance the fundamental understanding of microRNAs and microRNA expression in association with MDV infection post-vaccination, this study was designed to profile miRNAs and to identify miRNAs with dysregulated expression in the primary lymphoid organ, bursa of Fabricius, in the two genetically divergent inbred lines of chickens in response to a very virulent plus MDV (vv+MDV) challenge post-vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The small RNA_Seq reads that passed QC were analyzed following the similar procedures described earlier ( Zhang et al., 2020a ). Briefly, the pass-filter ( PF ) reads (the number of clusters that passed Illumina's “Chastity filter”) were analyzed with miRDeep* software package (v3.8) using the default parameters ( An et al., 2013 ) except the adapter sequence and chicken genome-specific index files.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccines are one of the most significant inventions in improving human health, with great importance being placed on the development of biomarkers that assess the safety and efficacy of vaccine candidates. Altered miRNA expression has been linked to immunological parameters of several infectious diseases after vaccination, such as Marek’s disease [9] , respiratory syncytial virus [10] , and pandemic influenza [11] . Besides infectious diseases, emerging evidence indicates that miRNAs could also influence the effectiveness of cancer vaccines, such as those for breast cancer [12] , colorectal cancer [13] , and melanoma [14] .…”
Section: Introductionmentioning
confidence: 99%